Metal‐Directed Self‐Assembly of a Polyoxometalate‐Based Molecular Triangle: Using Powerful Analytical Tools to Probe the Chemical Structure of Complex Supramolecular Assemblies. Issue 52 (25th November 2015) - Izzet, Guillaume; Macdonell, Andrew; Rinfray, Corentin; Piot, Madeleine; Renaudineau, Séverine; Derat, Etienne; Abécassis, Benjamin; Afonso, Carlos; Proust, Anna
Abstract: A polyoxometalate‐based molecular triangle has been synthesized through the metal‐driven self‐assembly of covalent organic/inorganic hybrid oxo‐clusters with remote pyridyl binding sites. The new metallomacrocycle was unambiguously characterized by using a combination of 1 H NMR spectroscopy, 2D diffusion NMR spectroscopy (DOSY), electrospray ionization travelling wave ion mobility mass spectrometry (ESI‐TWIM‐MS), small‐angle X‐ray scattering (SAXS) and molecular modelling. The collision cross‐sections obtained from TWIM‐MS and the hydrodynamic radii derived from DOSY are in good agreement with the geometry‐optimized structures obtained by using theoretical calculations. Furthermore, SAXS was successfully employed and proved to be a powerful technique for characterizing such large supramolecular assemblies. Abstract : Precise triangulation : A polyoxometalate‐based molecular triangle has been synthesized through the metal‐driven self‐assembly of covalent organic/inorganic hybrid oxo‐clusters with remote pyridyl binding sites. The new metallomacrocycle was unambiguously characterized by using 1 H NMR and 2D diffusion NMR spectroscopies (DOSY), electrospray ionization travelling wave ion mobility mass spectrometry (ESI‐TWIM‐MS), small‐angle X‐ray scattering (SAXS) and molecular modelling (see figure).